Centenarians Alleviate Inflammaging by Changing the Ratio and Secretory Phenotypes of T Helper 17 and Regulatory T Cells - Zhou, Lixing; Ge, Meiling; Zhang, Yan; Wu, Xiaochu; Leng, Mi; Gan, Chunmei; Mou, Yi; Zhou, Jiao; Valencia, C Alexander; Hao, Qiukui; Zhu, Bin; Dong, Biao; et al. (Frontiers in Pharmacology, 2022)
The immune system of centenarians remains active and young to prevent cancer and infections. Aging is associated with inflammaging, a persistent low-grade inflammatory state in which CD4+ T cells play a role. However, there are few studies that have been done on the CD4+ T cell subsets in centenarians. Herein, the changes in CD4+ T cell subsets were investigated in centenarians. It was found that with aging, the old adults had higher levels of proinflammatory cytokines and lower levels of anti-inflammatory cytokines in plasma. The levels of CRP, IL-12, TNF-α, IFN-γ, IL-6 and IL-10 were further increased in centenarians compared to old adults. While the levels of IL-17A, IL-1β, IL-23 and TGF-β in centenarians were closer to those in young adults. The total CD4+, CD8+, Th17 and Treg cells from peripheral blood mononuclear cells (PBMCs) were similar among the three groups. It was observed that the ratio of Th17/Treg cells was elevated in old adults compared to young adults. The ratio was not further elevated in centenarians but rather decreased. In addition, the ex vivo PBMCs differentiation assay showed that increased Th17 cells in centenarians tended to secrete fewer proinflammatory cytokines, while decreased Treg cells in centenarians were prone to secrete more anti-inflammatory cytokines. These observations suggested centenarians alleviated inflammaging by decreasing the ratio of Th17/Treg cells and changing them into anti-inflammatory secretory phenotypes, which provided a novel mechanism for anti-aging research.